European VAT in the Digital Age Initiative - Machart, Jan; Procházka, Petr; Sato, Alexej, 1952-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Despite the significant importance of Value Added Tax (VAT) as a key revenue source for all EU Member States, the current European VAT system remains outdated and unfit for today´s digital reality, as it is prone to VAT fraud – often driven by excessive administrative burden borne by businesses. The VAT in the Digital Age (ViDA) initiative of the European Commission reflects these shortcomings, presenting a series of legislative proposals focused on modernising the current VAT system. The aim of this Master´s thesis is to assess these changes and to apply them to model examples of intra-Community trade. The thesis predominantly utilises the analytical-synthetic method. Starting with a theoretical background, the ViDA legislative proposals were analysed, introducing in detail the new digital reporting requirements based on electronic invoicing, the updated VAT treatment of the platform economy, and a series of measures to avoid multiple VAT registrations within the EU. These VAT policies are estimated to generate an additional EUR 18 billion in VAT revenue per year and reduce the EU VAT gap by approximately 4 p.p. over the first 10 years. A case study was then conducted, including several model examples accompanied by stakeholder analyses. The results clearly show that even though the ViDA legislative proposals may reduce the overall administrative burden by harmonising, simplifying, and streamlining VAT rules across the EU, the newly introduced VAT compliance obligations, including demanding record-keeping requirements, may partially outweigh the expected cost savings for businesses. However, as the analyses suggest, tax authorities are expected to experience a more positive impact, since enhanced cooperation between Member States should support more effective VAT control, fraud detection, and ultimately an increase in VAT revenue.
Nevertheless, the revealed remaining uncertainties need to be addressed, and sufficient resources should be allocated to ensure digital data protection.
Vedoucí práce: Petr Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses